Benign glandular cells in posthysterectomy vaginal smears: the incidence is higher than expected - (:unkn) unknown (WILEY, 2004)
In this study, we have investigated the frequency and clinical significance of glandular cells in posthysterectomy vaginal smears. The slides of vaginal cuff smears of 290 patients were reviewed. The glandular cells were categorized into three groups: (1) squamous metaplastic-like cells; (2) columnar endocervical-like cells; and (3) small round cuboidal cells. Glandular cells were found in 39 (13%) of the 290 vaginal smears. Group 1 type cells were seen in 76% (n = 30), group 2 type cells in 38% (n = 15) and group 3 type cells in 47% (n = 19) of the smears. In 19 (48%) of the smears combination of two or three groups were seen. The presence of glandular cells showed a strong association with inflammation/repair as a background finding in the smears. No correlation could be found between the presence of atrophy and history of chemotherapy or radiotherapy. Apart from these there was a prominent increase in reporting benign glandular cells after the application of the current Bethesda 2001 reporting criteria in our laboratory. As a result our study showed that the finding of glandular cells in posthysterectomy vaginal smears is more frequent than expected and most of them could be related to inflammatory and regenerative processes in the absence of a clearly identified underlying cause.
Keywords: glandular cells; posthysterectomy; vaginal smears; cytology; COLUMNAR